Managers' use of nursing workforce planning and deployment technologies: protocol for a realist synthesis of implementation and impact. Issue 8 (26th August 2016) - Burton, Christopher; Rycroft-Malone, Jo; Williams, Lynne; Davies, Siân; McBride, Anne; Hall, Beth; Rowlands, Anne-M; Jones, Adrian
Abstract : Introduction: Nursing staffing levels in hospitals appear to be associated with improved patient outcomes. National guidance indicates that the triangulation of information from workforce planning and deployment technologies (WPTs; eg, the Safer Nursing Care Tool) and 'local knowledge' is important for managers to achieve appropriate staffing levels for better patient outcomes. Although WPTs provide managers with predictive information about future staffing requirements, ensuring patient safety and quality care also requires the consideration of information from other sources in real time. Yet little attention has been given to how to support managers to implement WPTs in practice. Given this lack of understanding, this evidence synthesis is designed to address the research question: managers' use of WPTs and their impacts on nurse staffing and patient care: what works, for whom, how and in what circumstances? Methods and analysis: To explain how WPTs may work and in what contexts, we will conduct a realist evidence synthesis through sourcing relevant evidence, and consulting with stakeholders about the impacts of WPTs on health and relevant public service fields. The review will be in 4 phases over 18 months. Phase 1: we will construct an initial theoretical framework that provides plausible explanations of what works about WPTs. Phase 2: evidence retrieval, review and synthesis guided by the theoretical framework; phase 3: testing and refining of programme theories, to determine their relevance; phase 4: formulating actionable recommendations about how WPTs should be implemented in clinical practice. Ethics and dissemination: Ethical approval has been gained from the study's institutional sponsors. Ethical review from the National Health Service (NHS) is not required; however research and development permissions will be obtained. Findings will be disseminated through stakeholder engagement and knowledge mobilisation activities. The synthesis will develop an explanatory programme theory of the implementation and impact of nursing WPTs, and practical guidance for nurse managers. Trial registration number: CRD42016038132.